Strengthening of the insured’s attention offices of the comprehensive health insurance - Cabrejos-Pita, José (2019)
Until the last decade, access barriers and weak mechanisms of caution restricted the right to health of Peruvians. In 2009, the policy of Universal Health Insurance (AUS) was instituted. In 2013, the National Health Insurance Agency (SIS) Offices for health insurance consumer assistance (OAA) were set up to ensure compliance with the access, quality and gratuity of care for its affiliated. Between 2015 and 2018, the SIS and the SISTEC Program executed a project in five regions of the country that contributed to the strengthening of processes of assistance to the affiliated to SIS. The project has generated evidence on the contribution of the OAA to the AUS. There is a need for consensus and articulation between the sectorial organizations involved to the configuration of a system for the health consumer assistance and protection of their health rights.